Operational Planning at Klinik Harmoni Fisioterapi - Wibowo, Dimas Aryo; indradewa, Rhian; Abadi, Ferryal; Anindita, Rina (Journal Research of Social Science, Economics, and Management, 2026)
This study examines the operational planning system implemented at Klinik Harmoni Fisioterapi as an effort to develop integrated and technology-based physiotherapy services. The increasing prevalence of stroke and neuromusculoskeletal disorders has increased the demand for rehabilitation services that are efficient, measurable, and patient-centered. However, many physiotherapy clinics still experience operational limitations, including manual registration systems, unintegrated medical records, and ineffective service coordination. Therefore, this research aims to analyze the operational planning model of Klinik Harmoni Fisioterapi in integrating digital systems, physiotherapy technology, and service management within a smart clinic framework. This study employed a descriptive qualitative approach using a case study method. Data were collected through interviews, document analysis, and literature studies related to operational management, healthcare information systems, and physiotherapy services. The findings reveal that the implementation of digital registration, therapy scheduling, electronic medical records, robotic physiotherapy, hydrotherapy, and quality management systems significantly improves operational efficiency, service consistency, and patient experience. In addition, the integrated system supports better coordination among healthcare personnel and facilitates data-driven managerial decision-making. In conclusion, the operational planning model implemented at Klinik Harmoni Fisioterapi can serve as a strategic framework for the development of modern, sustainable, and technology-oriented physiotherapy services.